Personal Characters Management : Caring Spiritualitas Increased Nursing Practice Implementation in Aji Muhammad Parikesit Hospital Tenggarong Kutai Kartanegara - Anik Puji Rahayu; Ika Fikriah; Sholichin Sholichin; Ediyar Miharja; Iwan Samsugito (Fakultas Kedokteran, 2020)
Background It is important for nurses to recognize and integrate the dimensions of body, mind, and spirit in their daily clinical practice (Dossey, 2005). If the client's needs are not met in one of the dimensions that can cause health and welfare problems. 94% of patients visiting hospitals in the US believe that spiritual health is as important as physical health. The need to get the attention that understanding caring alone is not enough to make a nurse can provide good service. Based on Maslow's theory that a person will do his work in accordance with the level of his needs. Understanding of a nurse who is at the level 5 stage of self-actualization, actually only wants to provide satisfaction for the achievement of personal self-actualization. If only the understanding of the concept of nurses was already at level 6. The importance of changing the mindset of nurses with the concept of caring spirituality so that nurses are fully aware of the deepest heart to get true blessing and happiness when nurses care for patients and afterward. Result The survey results from the 6-month in-house training process were able to increase the caring spirituality of nurses, which in turn was able to increase the application of services in nursing in hospitals. AM Parikesit Tenggarong. Furthermore, it is expected that nurses must increase their knowledge and understand the true concept of caring spirituality and be able to apply it in providing nursing care services to patients.Keywords: caring, spiritualis, nursing practice,